2016
DOI: 10.15640/jehd.v5n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Technical College Teachers’ Communication and Its Impact on Student Motivation

Abstract: Minimal research exists related to what technical college students perceive as effective teacher communication and how their perception influences motivation. The purpose of this study was to examine the relationship between teacher communication and student motivation to complete specific technical college courses. A cross-sectional survey design was employed to collect data about teachers' communication and the degree of association with student motivation. The Teacher Communication Behavioral Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Literature [20] believes that teaching ability includes four parts: teaching organization and monitoring ability, ability to communicate and cooperate with students or other teachers, ability to use modern information technology, and teaching research ability. Literature [21] believes that educational ability is a kind of practical ability, which is the ability of teachers to conduct teaching research and carry out teaching practice activities on the basis of cognition, understanding, mastery, and application of teaching academics. Literature [22] believes that the structure of teaching ability should interpret the connotation of teaching ability and construct its multidimensional structure from the three disciplinary dimensions of pedagogy, psychology, and sociology.…”
Section: Related Workmentioning
confidence: 99%
“…Literature [20] believes that teaching ability includes four parts: teaching organization and monitoring ability, ability to communicate and cooperate with students or other teachers, ability to use modern information technology, and teaching research ability. Literature [21] believes that educational ability is a kind of practical ability, which is the ability of teachers to conduct teaching research and carry out teaching practice activities on the basis of cognition, understanding, mastery, and application of teaching academics. Literature [22] believes that the structure of teaching ability should interpret the connotation of teaching ability and construct its multidimensional structure from the three disciplinary dimensions of pedagogy, psychology, and sociology.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, students' perception of their teacher's communication behavior affects the motivation of the students. A study found out that four communication dimensions (challenging, nonverbal support, understanding and friendly, encouragement and praise) have a positive correlation between teacher communication and student motivation, and controlling communication and student motivation did not have a positive relationship with motivation (Armstrong et. al, 2016).…”
Section: Second Language Writing Anxietymentioning
confidence: 99%
“…On the other hand, so far, several studies have shown how teachers' communication strategies can help students' motivational processes (Armstrong & Hope, 2016;Akudo, 2020). In the case of PE, studies such as the one conducted by Sparks, Dimmock, Whipp, Lonsdale, and Jackson (2015) highlight how teacher behaviours such as teacher communication have a positive impact in students' experiences in PE in areas like mood, class engagement, intrinsic motivation, efficacy beliefs, and leisure-time.…”
Section: Introductionmentioning
confidence: 99%